Modernizing Storage Conditions for Fresh Osteochondral Allografts by Optimizing Viability at Physiologic Temperatures and Conditions. (December 2021) - Denbeigh, Janet M.; Hevesi, Mario; Paggi, Carlo A.; Resch, Zachary T.; Bagheri, Leila; Mara, Kristin; Arani, Arvin; Zhang, Chenghao; Larson, A. Noelle; Saris, Daniel B.F.; Krych, Aaron J.; van Wijnen, Andre J.
Objective . Osteochondral allograft (OCA) transplantation has demonstrated good long-term outcomes in treatment of cartilage defects. Viability, a key factor in clinical success, decreases with peri-implantation storage at 4°C during pathogen testing, matching logistics, and transportation. Modern, physiologic storage conditions may improve viability and enhance outcomes. Design . Osteochondral specimens from total knee arthroplasty patients (6 males, 5 females, age 56.4 ± 2.2 years) were stored in media and incubated at normoxia (21% O2 ) at 22°C or 37°C, and hypoxia (2% O2 ) at 37°C. Histology, live-dead staining, and quantitative polymerase chain reaction (qPCR) was performed 24 hours after harvest and following 7 days of incubation. Tissue architecture, cell viability, and gene expression were analyzed. Results . No significant viability or gene expression deterioration of cartilage was observed 1-week postincubation at 37°C, with or without hypoxia. Baseline viable cell density (VCD) was 94.0% ± 2.7% at day 1. At day 7, VCD was 95.1% (37°C) with normoxic storage and 92.2% (37°C) with hypoxic storage ( P ≥ 0.27). Day 7 VCD (22°C) incubation was significantly lower than both the baseline and 37°C storage values (65.6%; P < 0.01). COL1A1, COL1A2, and ACAN qPCR expression was unchanged from baseline ( P < 0.05) for all storage conditions at day 7, while CD163 expression, indicative of inflammatory macrophages and monocytes, was significantly lower in the 37°C groups ( P < 0.01). Conclusion . Physiologic storage at 37°C demonstrates improved chondrocyte viability and metabolism, and maintained collagen expression compared with storage at 22°C. These novel findings guide development of a method to optimize short-term fresh OCA storage, which may lead to improved clinical results.